Valuation of micro and small enterprises using the methodology multicriteria and method of discounted cash flow - Marcus Vinicius Andrade de Lima; Carlos Rogério Montenegro de Lima; Ademar Dutra; Ana Lúcia Miranda Lopes (Revista de Ciências da Administração : RCA, 2010)
This paper presents a contribution to the method of discounted cash flow methodology using multicriteria decision aid. This methodology incorporates qualitative variables and subjective to the traditional method of discounted cash flows used in valuation companies. To illustrate the proposed method was a descriptive study of exploratory nature applied to a multicase. The intervention was in Micro and Small Enterprises (MSE) from the chemical, pharmaceutical and tourism. As a result, the appraiser set the price of the business taking into account the result of mixing between the two methodologies.